George Christopher Archibald and the quest for the substance of monopolistic competition - Julien Gradoz (Duke University, Center for the History of Political Economy (CHOPE), 2024)
This article examines George Christopher Archibald's contributions to monopolistic competition theory, which he approached from multiple perspectives throughout his career. In the 1950s, he critiqued this theory for its vague definitions and for prompting several economists to abandon profit maximization by firms. In the 1960s, influenced by the debates at the LSE on falsificationism and qualitative economics, he analyzed this theory's capacity to generate testable predictions, sparking a controversy with Stigler and Friedman. Finally, in the 1970s, he incorporated the characteristics approach, popularized by Lancaster, into this theory, thereby contributing to the modern reformulation of the theory of monopolistic competition.
Keywords: B21; B41; D40; 330; monopolistic competition; George Christopher Archibald; qualitative economics; falsificationism; characteristics approach